2022
DOI: 10.3390/pharmaceutics14081671
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Based Adjuvants for Vaccines as Immunomodulators of the Innate and Adaptive Immune Response: Current Knowledge, Challenges, and Future Opportunities

Abstract: New-generation vaccines, formulated with subunits or nucleic acids, are less immunogenic than classical vaccines formulated with live-attenuated or inactivated pathogens. This difference has led to an intensified search for additional potent vaccine adjuvants that meet safety and efficacy criteria and confer long-term protection. This review provides an overview of protein-based adjuvants (PBAs) obtained from different organisms, including bacteria, mollusks, plants, and humans. Notably, despite structural dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 264 publications
0
24
0
Order By: Relevance
“…It has been observed that anti-N antibody levels were higher in severe COVID-19 patients compared to those with mild symptoms (40). Although anti-N antibodies were associated with prolonged symptoms after COVID-19 infection, higher levels of IgG anti-N in the first week of SARS-CoV-2 infection were linked to a shorter time to sustained symptom resolution (41). These findings suggest that using inactivated viruses in designing vaccines against SARS-CoV-2 may not be adequate when a durable response against the N protein of SARS-CoV-2 is required (37,42).…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that anti-N antibody levels were higher in severe COVID-19 patients compared to those with mild symptoms (40). Although anti-N antibodies were associated with prolonged symptoms after COVID-19 infection, higher levels of IgG anti-N in the first week of SARS-CoV-2 infection were linked to a shorter time to sustained symptom resolution (41). These findings suggest that using inactivated viruses in designing vaccines against SARS-CoV-2 may not be adequate when a durable response against the N protein of SARS-CoV-2 is required (37,42).…”
Section: Discussionmentioning
confidence: 99%
“…Users are prompted to define the number of epitopes for Bcell, CTL, and HTL, while also specifying user-defined linker sequences (18) between the epitopes and the N-terminus sequence. A variety of different options of protein adjuvants are provided for the user to select and include in the multi-epitope vaccine sequences (22)(23)(24)(25).…”
Section: Multi-epitope Vaccine Sequencesmentioning
confidence: 99%
“…The immunogenicity of antigenic proteins administered via oral mucosal inoculation alone is weak and is typically enhanced by the addition of specific adjuvants or vectors to achieve the desired effect. Different adjuvants, and even the same adjuvant with modified subunits, elicit different immune responses ( 11 ). Numerous adjuvants and vectors possess molecular structures that are recognized and targeted by innate immunity, such as lipopolysaccharides, the acidic components of membranes, basic peptidoglycan structures and non-methylated CpG structures ( 12 ).…”
Section: Mechanisms Of Oral Immunitymentioning
confidence: 99%
“…The key to a successful oral vaccine lies in enhancing oral antigen presentation in the gastrointestinal mucosa and inducing effective mucosal and systemic immune responses. A well-designed adjuvant and antigen carrier system can reduce the antigen dose required for inducing an optimal immune response and immune tolerance ( 11 ). It is also important to note that, in the development of oral vaccines, it is crucial to consider their ability to withstand the various pH levels encountered throughout the gastrointestinal tract and the presence of proteolytic enzymes that can degrade antigen proteins ( 2 ).…”
Section: Feasibility and Challenges Of Oral Vaccinesmentioning
confidence: 99%